The investigation on strength and flexural toughness of fibre cocktail reinforced self-compacting high performance concrete - Ding Yining (2009)
Based on the experimental results of the workability, the suitable fibre types (steel fibres, PP-fibres and fibre cocktail) and fibre dosages for fibre-reinforced-self-compacting-high-performance-concrete (FRSCHPC) were selected. To assess the influences of different fibres on the compressive strength, flexural toughness and failure patterns of beams and slabs, a series of experiments has been carried out and evaluated. The results show that the fibre cocktail – a combination of steel fibres and PP-fibres – can represent an optimal fibre reinforcement for self-compacting-high-performance-concrete.